Withania somnifera (L.) Dunal root extract alleviates formalin-induced nociception in mice: involvement of the opioidergic system. Issue 1 (February 2016) - Orrù, Alessandro; Casu, Maria Antonietta; Tambaro, Simone; Marchese, Giorgio; Casu, Gianluca; Ruiu, Stefania
Abstract : Withania somnifera (L.) Dunal extracts (WSEs) may possess therapeutic perspectives in the treatment of inflammation and pain. We aimed to evaluate the antinociceptive property of a WSE in the formalin test and to investigate the involvement of several neurotransmitter systems in this effect. The time spent licking the formalin-injected paw was recorded in CD1 mice after pretreatment with increasing doses of WSE. Also, c-Fos spinal cord expression and the effects of different compounds were investigated under these experimental conditions. Finally, the efficacy of WSE was analyzed following an injection of glutamate. WSE reduced the antinociceptive response during the tonic but not the acute phase of the formalin test and decreased formalin-induced c-Fos expression in spinal neurons. These effects were antagonized by the opioid antagonist naltrexone, whereas GABA, cannabinoid, δ-opioid, and nitric oxide compounds were ineffective. The administration of WSE also reduced nociception and c-Fos expression induced by glutamate injection. These results showed that WSE is effective in assays of chemical-induced nociception, indicating that this plant has potential valuable properties for the treatment of specific painful conditions. The antinocicetive effects of WSE in the formalin test appeared to be specifically mediated by the opioidergic system, although the involvement of the glutamatergic system cannot be excluded.